Tissue Engineering: Engineered 3D Cardiac Fibrotic Tissue to Study Fibrotic Remodeling (Adv. Healthcare Mater. 11/2017). Issue 11 (7th June 2017) - Sadeghi, Amir Hossein; Shin, Su Ryon; Deddens, Janine C.; Fratta, Giuseppe; Mandla, Serena; Yazdi, Iman K.; Prakash, Gyan; Antona, Silvia; Demarchi, Danilo; Buijsrogge, Marc P.; Sluijter, Joost P. G.; Hjortnaes, Jesper; et al.
Abstract : Ali Khademhosseini and co‐workers describe an engineered 3D fibrotic heart tissue, which is created by fabricating physiologically relevant cardiac tissues with native‐like mechanical properties in article number1601434 . Upon exogenous stimulation with profibrotic transforming growth factor beta‐1, these tissues reveal fibrogenic changes, such as collagen production, myofibroblast activation, and electrophysiological disturbances.